Determination of spray drift using multiple metal cations as tracers - Zabkiewicz, J.A.; Steele, K.D.; Praat, J.P. (New Zealand Plant Protection, 2008)
An alternative method to the use of dyes in spray drift estimation has been developed using different metal cations with each spray solution This removes the need to collect the targets until all the spray events have been completed Spray drift trials were conducted with a tractor plus boom over a grass sward with plastic tape as the collector to capture ground spray deposits The extracted deposits from the collectors were quantified by ICPMS The advantages of using cations are that they are stable very low levels of detection are possible analytical and operational costs are reduced and they are nonphytotoxic at operational amounts